(untitled) (Jagannath University Journal of Science, 2025)
Sleep paralysis is a unique occurrence where individuals awaken during the night but find themselves unable to move. Despite being a fairly common phenomenon, it remains insufficiently researched. Although the exact causes are unclear, several studies have explored potential factors contributing to this phenomenon. This study investigated the relationship between adverse childhood experiences (ACEs) and sleep paralysis (SP) in adults, focusing on the mediating role of depression. A personal information form and Bangla-adapted versions of the Comprehensive Child Maltreatment Scale for Adults, Waterloo Unusual Sleep Experience Questionnaire, and Depression Scale were administered to 100 young adults purposively selected from public universities in Dhaka. Results of correlation coefficients suggested that only adverse childhood experiences (i.e., sexual abuse) are significantly and positively correlated with sleep paralysis. Multiple regression analysis revealed that depression and sexual abuse were significant predictors, jointly explaining 25.1% of the variance in sleep paralysis. Depression alone accounted for 16.1% of the variance, while sexual abuse explained 8.9%. Furthermore, depression partially mediated the relationship between adverse childhood experiences and sleep paralysis, as supported by the Sobel test (p = .02). The outcomes of the present study are anticipated to serve as a valuable tool for mental health professionals and physicians in addressing issues related to sleep deprivation, subjective sleep quality, and sleep hygiene among their clients. This information can aid them in implementing necessary interventions to improve the sleep quality of adults. Jagannath University Journal of Science, Volume 11, Number 2, Dec. 2024, pp. 1−19